Brazilian private health system: history, scenarios, and trends - June Alisson Westarb Cruz; Maria Alexandra Viegas Cortez da Cunha; Thyago Proença de Moraes; Sandro Marques; Felipe Francisco Tuon; Arivelton Loeschke Gomide; Gisele de Paula Linhares (BMC, 2022)
Abstract Background Health care is a complex economic and social system, which combines market elements and public and social interest. This combination in Brazil, like systems in China and United States of America, is operationalized through the public and private system. The sector represents approximately 9% of the country's GDP, of which 56% is privately sourced and 44% is of public origin. In the private sector includes a structure with 711 private health institutions, 47 million beneficiaries and revenues of US$30 billion a year. Methods Therefore, this research describes and analyzes the complementarity of Private Health before the Brazilian Unified Health System, highlighting its main characteristics, scenarios, and trends in the face of the health system and the Brazilian market. This descriptive and exploratory research uses secondary data from various sources, submitted to quantitative data analysis methods. The object of the research is the history of private health in Brazil and its main actors. Results The data are organized into three groups, each with its approach of collection and analysis. Thus, it is perceived as the notorious growth of large operators, to the detriment of operators with a lower concentration of beneficiaries; the increasing concentration of the market through mergers and acquisitions promoted by large publicly traded corporations, especially in regions with a lower rate of private health coverage; and the growth of the sector through business plans, whose central characteristic is the dependence on the country's employability rate. Conclusions It is possible to perceive an intense trend of concentration of Brazilian private health in large institutions that have capitalized and have a great appetite for growth through mergers and acquisitions, whether from smaller operators or health institutions that integrate their health networks, following complementary health models already consolidated in countries such as China, and the United States of America, among others. This concentration projects a market with fewer options and competitiveness, reduction in transaction costs and increase the operational effectiveness of health care.